Climber, mediator, and marathoner: narrative inquiry of career motivation changes of pre-service CSL teachers throughout teaching practicum - Zhou, Rubing; Wang, Tianmiao; Lin, Hanzhao (Frontiers in Psychology, 2024)
Currently, there exists a contradiction between the growing demand for foreign language learning worldwide and the shortage of second language teachers. In the field of Chinese as a second language education, despite the increasing number of pre-service CSL teachers, only a minority choose to continue in the profession after completing teacher education courses. To explore the reasons behind this phenomenon, this longitudinal narrative inquiry examined the changes in career motivations of three participants in teaching practicum, and discussed key narrative clues based on metaphors emerging in the narratives. The research found that participants' career motivations were influenced by teaching practice and underwent different dynamic changes. Among them, self-efficacy and intrinsic self-fulfillment motivation are the core motivational factors governing participants' career choices, with the unique cross-cultural motivation of second language teachers also playing a role. Additionally, the study highlights the important role of narratives and metaphors in understanding changes in teacher career motivations.